WANITA KARIR DALAM PERSPEKTIF HUKUM ISLAM - Nasution, Adanan Murroh (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2020)
This paper describes about women who work outside the home, known as career women, as the main focus of the problem in this paper is how is the view of Islamic law towards career women. So to answer this problem the authors use the literature study method by tracing the opinions of scholars about career women from various literatures.The findings, that in Islam some scholars allow women to work outside the home to become career women, namely women who are able to manage their lives to achieve success, both in professional life (work in the office) and in fostering their households.